The Mortality After Release from Incarceration Consortium (MARIC) study: Strengths of international data linkage - Rohan Borschmann (International Journal of Population Data Science, 2018)
Introduction Adults released from incarceration experience complex physical and mental health problems, and are at markedly increased risk of preventable death. Despite this, not enough is known about the granular epidemiology of mortality in this population to inform development of targeted, evidence-based responses.